The Influence of Children on Family Purchasing in Lithuania and Azerbaijan - Dikčius, Vytautas; Armenakyan, Anahit; Urbonavicius, Sigitas; Jonynienė, Gintarė; Gineikienė, Justina (Organizations and Markets in Emerging Economies, 2014)
In the context of marketing, children are considered to be increasingly important influencers of parents’ purchasing decisions. However, their influence varies depending on the products and cultures, and many particularities of this phenomenon remain under-researched. This is especially true in regard to the countries that are categorized as “emerging economies”. Some of them still do not have reliable measurements of their cultural dimensions, and this increases difficulties in performing comparative analysis there. On the other hand, these countries offer a broad and important scene for child influence studies.This study concentrates on analysis and comparisons of children’s influence on parental purchase decision-making in Lithuania and Azerbaijan. These countries are different in, at least, two Hofstede’s cultural dimensions that are important in family decision-making: individualism and uncertainty avoidance. Also, the study contributes to the existing research by using a product use-related categorization of product groups.Such an approach reveals significant difference in terms of how children exert their influence on purchasing services versus tangible products for the family use. Interesting differences between the countries in terms of children’s influence on purchasing products for their personal use also opens a new scene for future studies that might consider a similar product categorization approach.